PENDUGAAN POTENSI DAN PRODUKTIVITAS NIRA AREN DI HUTAN KEMASYARAKATAN (HKM) BINAWANA - Dimas Adi Pratama; duryat duryat; Hari Kaskoyo (University of Lampung, 2022)
Non-timber forest products (NTFPs) for palm plantations have high economic potential for farmers. The productivity of sap on sugar palm plants is very important to study to determine policy directions that can help the community's economy. Sugar palm plants in the productive age group are only 38 stems with the highest level of production occurring in the 5-8 year age class with the production of sap per tree reaching 47,727 liters by the year. The total productivity of sap produced in one year reaches 43,908,573 liters. Sugar palm plants can be tapped since the age of 5 years and have been productive at the age of 7 years. The economic potential obtained by palm farmers in one year is Rp56.071.061 or Rp4.672.588/month. However, there are fewer productive sugar palms than post productive plants, so farmers need to regenerate plants to increase the yield of existing sap.